A combined subunit vaccine comprising BP26, Omp25 and L7/L12 against brucellosis. Issue 8 (23rd January 2020) - Gupta, Sonal; Singh, Damini; Gupta, Manish; Bhatnagar, Rakesh
ABSTRACT: The current vaccines against brucellosis, namely Brucella abortus strains 19 and RB51, prevent infection in animals but pose potential risks like virulence and attenuation reversal. In this milieu, although subunit vaccination using a single potent immunogen of B. abortus, e.g. BP26 or Omp25 or L7/L12 etc., appears as a safer alternative, nonetheless it confers inadequate protection against the zoonosis compared to attenuated vaccines. Hence, we have investigated the prophylactic potential of a combined subunit vaccine (CSV) comprising the BP26, Omp25 and L7/L12 antigens of B. abortus, in mice model. Sera obtained from CSV immunized mice groups showed heightened IgG titers against all the three components and exhibited specificity upon immunoblotting, reiterating their authenticity. Further, the IgG1/IgG2a ratio obtained against each antigen revealed a predominant Th2 immune response in CSV immunized mice group. However, on assessing the levels of Th1-dependent (IFN-γ and TNF-α) and Th2-dependent (IL-4 and IL-10) cytokines in different formulations, prominent IFN-γ levels were elicited in CSV immunized mice. Further, upon infection with virulent B. abortus 544, the combined subunit vaccinated mice displayed superior degree of protection (Log10 reduction) than the individual vaccines; however, B. abortus S19 showed the highest protection. Altogether, this study suggests that co-immunization of three B. abortus immunogens as a CSV complements and triggers a mixed Th1/Th2 immune response leading to superior degree of protection against pathogenic B. abortus 544 infection. Abstract : Co-immunization with three B. abortus immunogens as a combined subunit vaccine (CSV) effectively protects mice against pathogenic B. abortus 544 infection.